High-Performance human resource practices: implications for discretionary work behaviour in higher educational institutions - Odoch, Hojops; Mukoza, Monica Mirembe; Kayondo, Barbara N.; Namono, Rehema (Emerald, 2024)
Purpose Higher education institutions discretionally participate in THE training of citizens for a sustainable world. Empirical evidence argues the synergetic effect of high-performance human resource practices (H-PHRPs) on its outcomes. Scholars have, however, questioned the appropriateness and applicability of H-PHRPs in developing economies, one of the eye-catching debates being the implicit universality of H-PHRPs. Literature has also banded the H-PHRPS and established the antecedent role of H-PHRPS on its outcomes. This study aims to examine the relative importance of H-PHRPs on discretionary work behavior (DWB) using a sample from public university employees to confirm the external validity of H-PHRPS constructs by replicating the findings in an Eastern setting and, more so, a developing nation like Uganda. Design/methodology/approach In the study, the authors used relative analysis to determine the role of H-PHRPs in enhancing DWB. The authors examined performance-based compensation, employee training and development, employee empowerment, competence-based performance appraisal and merit-based promotion as the H-PHRPs. The authors selected a sample of employees from Ugandan Universities used an explanatory study design to test the antecedent role of H-PHRPs on DWB. Findings The research results show that individual H-PHRPs significantly affect DWB. As regards the relative importance of H-PHRPs on DWB, the findings further reveal that H-PHRPs predicts DWB over and above its individual components. Research limitations/implications The authors gathered the data from public universities; therefore, when applied to a scenario of private universities, the conclusions might not hold up. Therefore, to confirm the results of the current study, future research can take private universities into account. Although, the study was cross-sectional, high performance human resource strategies in an organization may evolve over time. This work paves the way for future longitudinal studies in the same field of study. Practical implications This research presents an understanding justification for human resources management strategies. Organizations’ managers should improve the morale of their employees through various management practices by strategically devising human resource practices geared toward enhancing employee DWB. Organizational managers ought to prioritize the high-performance practices in order of relative importance in enhancing employee DWB. By prioritizing human resource practices, like training and pay for performance, universities are able to proportionately direct distinctive focus on human resource practices that enhance employee behaviors. Originality/value The findings of the research have both empirical and theoretical significance. This is an innovative study that aims to determine the relative relevance of H-PHRPs on DWB by using a sample taken from Ugandan public universities which is a developing nation. From a theoretical standpoint, the study enhances the practicability of the social exchange theory by establishing that employees exhibit DWB to reciprocate the organization for the H-PHRPs provided by the organization.